Portugal e o padrão alimentar mediterrânico. - Durão, Catarina (2008)
Objectives: We proposed to evaluate Portugal's food availabilities compared to the availabilities of four Mediterranean countries (Greece, Spain, Italy and France). Furthermore, we proposed to evaluate if Portugal's food availabilities were (or are) near to the ones described as typical of the Mediterranean Diet. Methods: Data from four decades (1961-2000) of FAO's Food Balance Sheets was analyzed. We also compared Portugal's availabilities with data from two well known studies (Seven Countries and EURATOM studies). Results: Where it concerns the data from FAO's food balance sheets, there was a group of countries (Portugal, Greece, Italy, Spain and France) with similar availabilities. As for the comparison between Portugal and data from the two mentioned studies, we observed an alternated proximity Portugal - Greece / Portugal - South of Italy. Conclusions: In the 60's there was a group of countries with avalabilities close to the ones described for the Mediterranean Diet. This situation changed over time.